Riverine plastic litter monitoring using unmanned aerial vehicles (UAVs) - Geraeds, Marlein; van Emmerik, Tim; de Vries, Robin; Ab Razak, Mohd Shahrizal (MDPI, 2019)
Plastic debris has become an abundant pollutant in marine, coastal and riverine environments, posing a large threat to aquatic life. Effective measures to mitigate and prevent marine plastic pollution require a thorough understanding of its origin and eventual fate. Several models have estimated that land-based sources are the main source of marine plastic pollution, although field data to substantiate these estimates remain limited. Current methodologies to measure riverine plastic transport require the availability of infrastructure and accessible riverbanks, but, to obtain measurements on a higher spatial and temporal scale, new monitoring methods are required. This paper presents a new methodology for quantifying riverine plastic debris using Unmanned Aerial Vehicles (UAVs), including a first application on Klang River, Malaysia. Additional plastic measurements were done in parallel with the UAV-based approach to make comparisons between the two methods. The spatiotemporal distribution of the plastics obtained with both methods show similar patterns and variations. With this, we show that UAV-based monitoring methods are a promising alternative for currently available approaches for monitoring riverine plastic transport, especially in remote and inaccessible areas.